TINJAUAN HUKUM MENGENAI HAK CIPTA SEBAGAI HAK MORAL YANG MERUPAKAN HAK EKSKLUSIF TERHADAP PENCIPTA LAGU: LEGAL REVIEW ON COPYRIGHTS AS A MORAL RIGHT THAT IS AN EXCLUSIVE RIGHT AGAINST THE SONG CREATORS - Irene Svinarky; Padrisan Jamba (Asosiasi Ide Bahasa Kepri, 2022)
Copyright is one of the Intellectual Property Rights (IPR) that aims to provide protection to the creator. When discussed about the ownership of a copyright song is different from other rights in IPR, especially regarding moral rights that actually need to be obtained by the songwriter. Therefore, the author is interested in taking the title of Legal Review regarding Copyright Regarding Moral Rights as One of the Exclusive Rights To Songwriters. Based on the title, the purpose of the research raised is: To find out the moral rights obtained by songwriters based on laws and regulations. This research is used Qualitative method. The nature of this research is descriptive, namely by studying, explaining the rules related to the problems raised. In addition, in the writing taken secondary data by collecting data from the library, then using data materials such as: First, primary data materials are regulations related to Copyright; Second, secondary data materials are books, papers, thesis, journals related to Copyright; Third, tertiary data material is an English dictionary.